EFFECTS OF RECOMBINANT FOLLICLESTIMULATING HORMONE (GONAL F) VERSUS H U M A N MENOPAUSAL G O N A D O T R O P H S (PERGONAL) IN BIOLOGICAL AND CLINICAL OUTCOMES OF IVF A N D ICSI - Kaluarachchi, A; Senevirathne, H R; Wijeratne, S; Nelson, C; Lankeshwara, D (My University, 2012)
To compare the effectiveness of rFSH (Gonal F) with hMG (Pergonal) in IVF and ICSI cycles. Method: The biological and clinical outcomes of two age matched samples from women using Gonal F and Pergonal were analyzed. The total numbet of FSH vials used in a stimulation cycle, numbet of eggs retrieved, fertilization rates and number of pregnancies were analyzed. Results: There was no statistically significant difference between the mean numbers of FSH vials used (FSH = 45.5 yials Vs h M G = 39.7 vials, P> 0.05) There was no significant difference between the mean number of eggs retrieved. (rFSH = 7 8 Vs fiMG = 7.7, P>0.05). The mean remiization rate was significantly higher with hM G compared to rFSH (hMG=75.0% Vs rFSH = 56.8%, P<0.05) Clinical pregnancy rates were higher in rFSH group (23.7%) when compared to hM G group (13.2%), but this was not statistically significant. (x2= 1.40, df= 1, p>0.05) The cycle cancellation rates due to inadequate stimulation were similar in both groups (0.5%) Conclusion: Biological out comes of both rFSH and hM G ate comparable. Type of FSH used appears to be one of the factors determining clinical outcome. Further evaluation in this tegard is recommended.